The Role of Human Resources during Acquisition in an International Company - Andriianova, Anastasiia (2017)
The topic of this thesis is dedicated to Human Resources role during a corporate acquisition in the company. The author has 3 years of HR experience from an international company that contributes to better understanding and clearer insight. Recently, acquisitions occur frequently, and companies do not always pay the appropriate attention to Human Resource issues that in turn, cause the decline of morale and culture. This results in the loss of key talent. In addition, this costs the company its reputation and possible decrease in profit. One can obtain the best technologies, but will not be able to succeed without employees who are satisfied with their employer and are dedicated to their job. The thesis is divided in two sections. In the first section, the author collects the most relevant knowledge from academic and business sources related to the topic. In the second section, the role of Human Resources during the turbulent time of acquisition is explored based on the example of one international company. The author describes the culture in this company, and also how the HR structure changed to be able to serve corporate objectives after the acquisition. Two surveys are conducted in this company among HR leaders and employees from Prague office. Based on the analysis of the surveys, author own observations and informal interviews with senior HR professionals, the author proposes valuable recommendations and suggestions for the most critical areas in which HR responsibilities are fundamental.